Follow the actors: Ethnographic keys for understanding legal activism for criminal justice reform in Argentina - Mira, Julieta (2019)
This article presents the research backroom about the legal activism in the criminal justice system reform following the ethnographic strategy. In particular, it addresses the “struggle” for “accusatory” criminal procedural reform at the federal level in Argentina since the end of the last dictatorship (1976-1983). Specifically it is about: a) participation in public events as an entrée to the field; b) native etnographer; c) native categories and theoretical concepts; d) the cause-based “partisanism” (militancia) and legal activism; and e) reform flags as cosmologies of social order. Finally, the article offers an analysis of the benefits of ethnographic research with legal activists in the field of human rights.